eTOM to NFV mapping for flexible mobile service chaining in 5G networks: IMS use case - Youssef Seraoui; Brahim Raouyane; Mostafa Belmekki; Mostafa Bellafkih (Heliyon, 2020)
Mobile network operators (MNOs) continually look to improve their business and become more agile and competitive within the quickly developing telecommunications industry. In turn, telecommunication professionals put forward and adapt advanced models and frameworks to assist MNOs to achieve their goals. In this context, the Business Process Framework (eTOM) was established by the TeleManagement Forum and on which we base this work to suggest a mapping of this eTOM business process model upon the network functions virtualization (NFV) framework. Thereby, the main purpose is to design a hybrid architecture by the combination of the aforementioned frameworks for dynamic service delivery with improved resource performance and quality of service so as to fulfill some of the purposes of the 5 generation (5G) technology with regard to a telecommunication system managed and orchestrated in a virtualized environment. Indeed, MNOs will be in a position to scale mobile services up and down fast and reduce costs to better align them with network usage. These procedures are performed based on flexible service chaining through implemented NFV management and orchestration modules along with SDN controller functions. In this article, we outline possible designs and analyses of flexible mobile service chaining to support end-to-end network slicing for dynamic service provisioning in order to provide a novel approach in the framework of the 5G technology, more especially from data and signaling based network perspectives. We project our proposal onto the IP Multimedia Subsystem (IMS) core network to discuss both dynamic and static signaling service provisioning approaches. In this situation, we set up a testbed platform with the goal of assessing the behavior of a virtualized IMS system, in a static signaling service provisioning environment through two signaling service chains to validate part of our proposed approaches. Experiment results confirm that virtualized IMS signaling resource performance indicators could be enhanced in the case of unpredicted performance degradation of one of the virtualized signaling resources assigned to the IMS virtual network functions composing the main signaling service chain by instantiating a second signaling service chain. Finally, IMS application performance indicators are improved regarding registration delay and session setup time.